The pedagogical aesthetic culture, didactic strategies in teaching performance (Original) (Revista científica Olimpia, 2019)
The theme of this article is related to pedagogic aesthetic culture and teaching strategies in the performance of teachers. The objective is to identify the weaknesses and strengths in the use of methodological strategies in the area of ​​cultural and artistic education. We used scientific and empirical methods such as deductive, inductive, analysis and syntheses, as well as statistics, the sample used was 22 teachers and 30 students, the most outstanding results are; mel 73% of teachers consider that the knowledge of aesthetic education and management of the curriculum of Cultural and Artistic Education significantly influences the performance in the classroom, Likewise 77% of teachers do not handle the ECA Curriculum, all the sublevels of EGB, 73% of teachers, have not been trained in teaching strategies in the subject of cultural and artistic education since the use of them energize the classes, while 93% of students say that the teacher of the subject Cultural and artistic education makes him work alone, that is, they do not apply active techniques for teaching and learning to develop skills with performance criteria in the subject of cultural and artistic education.
Keywords: aesthetic culture; didactic strategies; teaching performance